BONE CHIP, UV-C IRRADIATION AND LATEX GLOVES: How To Prepare A Bone Sample For Ancient DNA Analyses - Scholz, Michael; Pusch, Carsten M. (Hukay; Vol 2 No 1, 2014)
Within the last decade the young discipline of palaeogenetics has developed to a successful and expectant field of archaeobiological research. In the following article we give main advice on treatment and preparation of prehistoric bone samples when further analyses on molecular level are required. We demonstrate which precautions, working conditions, and monitoring protocols are necessary to avoid or at least minimize contamination with nucleic acids of any source. By following the catalog of proposed guidelines a major step towards the generation of authentic results (e.g. DNA sequence data) is done.